The Strategic Role of Rumah Tahfidz in Strengthening Islamic Education in Sungai Penuh City: Addressing Contemporary Educational Challenges - Mukhlis Mukhlis; Amelia Yetri (Muslim Education Review, 2026)
Globalization, increasingly erodes spiritual values and demands religious education to serve as a moral fortress in addressing contemporary challenges. As a religious education institution, Rumah Tahfidz plays a strategic role in fostering young generations by strengthening Qur'anic memorization and the internalizing Islamic values. This study analyzes the role of Rumah Tahfidz in enhancing the quality of Islamic religious education in Sungai Penuh City using a Mixed-Methods approach with a Sequential-Explanatory design. Quantitative data were obtained through surveys involving 110 respondents, consisting of administrators, teachers, and students. Qualitative data were collected through interviews, observations, and document studies involving 16 participants, including administrators, teachers, students, and parents. The results indicate that curriculum and teaching methods (X1=0.448), teacher competence (X2=0.548), and infrastructure and facility support (X2=0.615) significantly influence the quality of religious education, with a coefficient of determination of 79.4%. Qualitative findings emphasize that optimizing the role of Rumah Tahfidz can be achieved through four key strategies:(1)Curriculum and teaching method innovation integrating technology without abandoning traditional essence,(2)Enhancing teacher and administrator competence through technology-based pedagogical training,(3)Strengthening infrastructure and sustainable funding,(4)Collaboration between Rumah Tahfidz, the community, government, formal educational institutions, and religious organizations. These strategies are expected to reinforce the role of Rumah Tahfidz as a pivotal pillar of religious education in the contemporary era.